Skeletal muscle‐specific over‐expression of the nuclear sirtuin SIRT6 blocks cancer‐associated cachexia by regulating multiple targets - Sadhana A. Samant; Vinodkumar B. Pillai; Mahesh P. Gupta (Wiley, 2021)
Abstract Background During cancer cachexia, cytokines released from tumour cells can alter body's metabolism, which can lead to onset of this disease process. Biological basis of cachexia is multifactorial; hence, it is important to identify and modulate multiple targets to curtail the process of cachexia. Previously, we reported that the nuclear sirtuin, SIRT6, blocks expression of myostatin, a negative regulator of muscle growth, through modulation of the NF‐κB signalling. This study was undertaken to test whether muscle‐specific over‐expression of SIRT6 can block the cancer‐associated muscle wasting in vivo and to identify additional relevant targets of SIRT6, which can explain its ability to maintain muscle health. Methods We generated a skeletal muscle‐specific SIRT6 over‐expressing transgenic mouse line (Sk.T6Tg) expressing SIRT6 at a moderate (two‐fold to four‐fold) level, compared with its control littermates. To generate a cancer‐cachexia model, B16F10 mouse melanoma cells were injected subcutaneously in the flanks of mice. Gastrocnemius muscle tissues from non‐tumour and tumour controls and Sk.T6Tg mice (n = 5-20) were analysed by histology, immunoblotting, and RT‐qPCR. Plasma samples of mice were evaluated using cytokine arrays and ELISA in both non‐tumour and tumour conditions. Results Our results demonstrate dual benefits of muscle‐specific moderate over‐expression of SIRT6 in a mouse model of cancer‐cachexia. In tumour‐bearing mice, SIRT6 over‐expression preserved muscle weight (P < 0.001) and fibre size (P < 0.005) as well as suppressed tumour growth (P < 0.05). SIRT6 over‐expression significantly reduced myostatin expression and plasma free fatty acids levels but maintained plasma insulin levels in tumour‐bearing mice. These positive effects of SIRT6 were associated with downregulation of the circulatory chemokine, CXCL10, and the myokine, WNT4. SIRT6 also upregulated expression of GLUT4, the major glucose transporter in the skeletal muscle. These results for the first time demonstrate that SIRT6 regulates multiple targets to limit tumour growth and cancer‐associated muscle atrophy. Conclusion Given the multifactorial nature of cachexia, SIRT6, which concurrently controls multiple pathways, can be a valuable therapeutic target to overcome this debilitating syndrome.